(untitled) - Milsom, Ian (Amsterdam, 2006)
EUROPEAN PRACTICE IN GYNAECOLOGY AND OBSTETRICS is a series of books conceived and endorsed by the European Board and College of Obstetrics and Gynaecology (EBCOG). The authors present treatments for which a consensus exists and - when there is no consensus - they discuss the key elements of the controversy. Each book provides a review of the basic science, recent concepts in pathophysiology, clinical aspects, treatment and unresolved problems or controversies,A final section provides multiple-choice questions for each chapter. * Series concentrates on important and changing areas of clinical practice * Each volume editor is a leading European expert in the field * Contributors are drawn from a wide range of European countries * All volumes include a review of basic science and pathophysiology, as well as clinical aspects, treatment, unresolved problems * Current references are included for each chapter * Multiple choice questions are provided at the end of each chapter
Keywords: Contraception,Birth control,Phương pháp tránh thai,Sinh đẻ có kế hoạch